Changes in ruminal fermentation and microbial population of feedlot Nellore cattle fed crude glycerin and virginiamycin - Castagnino, Pablo S. [UNESP]; Dallantonia, Erick E. [UNESP]; Fiorentini, Giovani [UNESP]; Vito, Elias San [UNESP]; Messana, Juliana D. [UNESP]; Lima, Laís O. [UNESP]; Simioni, Tiago A. [UNESP]; Berchielli, Telma T. [UNESP] (Elsevier, 2018)
The objective of this experiment was to evaluate the effects of crude glycerin (CG) and virginiamycin (VM) diets on ruminal fermentation and microbial population of feedlot Nellore cattle. Eight rumen fistulated bulls (BW = 600 ± 34 kg; 26 ± 3 months) were used in a replicated 4 × 4 Latin square (21-d periods) with 2 × 2 factorial arrangement of treatments: diets without virginiamycin (VM−) or virginiamycin at 25 mg/kg DM (VM+) combined with diets without crude glycerin (CG−) or CG (80% glycerol) at 100 g/kg DM (CG+). The sugar cane bagasse was used as the exclusive roughage in the proportion of 200 g/kg in dry matter of diet and crude glycerin replaced corn in the diet formulation. Ruminal samples were collected immediately before feeding and at 3, 6, 12 and 18 h post feeding on days 20 and 21 of the sampling week. Data were analyzed in a replicated 4 × 4 Latin square with a 2 × 2 factorial using the MIXED procedure of SAS (SAS Inst., Inc., Cary, NC). There were no CG × VM interactions for any variable measured (P ≥ 0.10). The intake of DM had a tendency to be greater in CG+ than CG− diets (P = 0.07). Apparent total tract digestibilities of nutrients were similar among diets (P ≥ 0.10). Diets with CG or VM had similar values of pH (mean = 6.15; P ≥ 0.10). Data showed that CG or VM did not affect the concentration of total VFA (116.92 mM; P ≥ 0.10). The proportion of propionate increased 27.5% in CG+ diets, regardless of VM inclusion (P = 0.01). Acetate:propionate ratio was lower in CG+ compared to CG− diets (3.58 vs. 2.12; P ≥ 0.10). Valerate and butyrate proportion was greater in CG+ than CG− diets (P < 0.05). The inclusion of VM or CG did not alter the relative abundance of fibrolityc bacteria (P ≥ 0.10). Total protozoa counts (P = 0.052) and Metadinium spp. (P = 0.058) had a tendency to decrease in VM+ than VM− diets (P < 0.10). Crude glycerin had positive effects on rumen fermentation products and can replace virginiamycin with increment of Megasphaera elsdenii abundance. However, combining virginiamycin and glycerin does not affect positively rumen fermentation and growth of bacteria that metabolize lactate.
Keywords: Beef cattle; Crude glycerin; Fermentation; Finishing diets; Virginiamycin